2022
DOI: 10.5194/acp-22-14189-2022
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-derived constraints on the effect of drought stress on biogenic isoprene emissions in the southeastern US

Abstract: Abstract. While substantial progress has been made to improve our understanding of biogenic isoprene emissions under unstressed conditions, large uncertainties remain with respect to isoprene emissions under stressed conditions. Here, we use the US Drought Monitor (USDM) as a weekly drought severity index and tropospheric columns of formaldehyde (HCHO), the key product of isoprene oxidation, retrieved from the Ozone Monitoring Instrument (OMI) to derive top-down constraints on the response of summertime isopre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 76 publications
1
7
0
Order By: Relevance
“…This indicates more OA formations per unit increase in sulfate as drought deteriorates. The higher sensitivities of OA to sulfate under droughts can be explained by increasingly higher isoprene concentrations as shown in our previous studies in the SEUS (Wang et al, 2022b;Li et al, 2022), resulting in more IEPOX in the atmosphere to be further converted to particle phase catalyzed by sulfate. The intercept of the linear regression can be interpreted as other OA components that are not associated with sulfatecatalyzed IEPOX SOA, such as POA and anthropogenic SOA (Malm et al, 2017).…”
Section: Regional Analysis In the Pacific Northwest And Southeast Ussupporting
confidence: 52%
“…This indicates more OA formations per unit increase in sulfate as drought deteriorates. The higher sensitivities of OA to sulfate under droughts can be explained by increasingly higher isoprene concentrations as shown in our previous studies in the SEUS (Wang et al, 2022b;Li et al, 2022), resulting in more IEPOX in the atmosphere to be further converted to particle phase catalyzed by sulfate. The intercept of the linear regression can be interpreted as other OA components that are not associated with sulfatecatalyzed IEPOX SOA, such as POA and anthropogenic SOA (Malm et al, 2017).…”
Section: Regional Analysis In the Pacific Northwest And Southeast Ussupporting
confidence: 52%
“…In addition, these findings suggest that the effect of water stress on isoprene emissions differs from one region to another. Using OMI HCHO columns over the South-Eastern United States, Wang et al (2022) found that HCHO is 6% higher during mild drought and 23% during severe droughts. These results support future developments in biogenic emission models to implement algorithms able to reproduce both regimes (mild/short water stress, increasing emissions; severe/long water stress, decreasing emissions) and different vegetation/region sensitivity to water stress.…”
Section: Discussionmentioning
confidence: 99%
“…We observe HCHO columns going up in the northwestern US and over oil sands in Canada, possibly due to increased evergreen needleleaf forest and an increase in crude oil production (Zhu et al, 2017), respectively. The downward trends over the southeast US could be due to a decrease in drought events (Figure S5), which significantly affect isoprene emissions and the oxidation of VOCs (Duncan et al 2009;Naimark et al, 2021;Wang et al, 2022). Alternatively, this downward trend could be partially due to the dampened HCHO production from VOC oxidation due to reduced NOx emissions (Marais et al, 2014;Wolfe et al, 2016;Souri et al, 2020c).…”
Section: Total Hcho Columnsmentioning
confidence: 99%